Rethinking Mediumship in Contemporary Wenzhou - Pan, Junliang (Review of Religion and Chinese Society, 2019)
The study of spirit mediums has drawn the attention of international scholars from the 1960s onward, and the topic continues to thrive. Yet little work has been done on spirit mediums in mainland China, which have mainly been glimpsed through studies of mediumship in Taiwan. This article draws on ethnographic research to explore the diverse traditions of spirit mediums in Wenzhou. While spirit mediums are viewed with ambivalence, they play a significant role within broader Chinese folk religions. It is crucial to understand spirit mediums through the appropriate cultural context in order to understand their diverse practices and roles in local society. I discuss why Wenzhou’s mediumship should be regarded as a form of shamanism in spite of differences between its discourse and practices and those of Minnan mediumship, as well as those of Siberian or Korean shamanism.